Remarks at Plenary Session, Third International Conference on Financing for Development, Addis Ababa, Ethiopia, July 13, 2015 - Kim, Jim Yong (2016)
Remarks delivered by Jim Yong Kim, President of the World Bank Group, discuss building on Ethiopia’s legacy by presenting the world with a shared vision for substantially increasing funding for the world’s poor. He talks about the need to be bold, creative, form strong partnerships, and find new resources to meet our goals of reducing poverty in the world. He talks about how the funding we leverage means more children will be educated, more patients will be treated, and more vital services will be provided. He concludes that we are part of a growing global movement that is the first generation in humankind that can end extreme poverty.